Thymol: Effects on reproductive biology and Gene's organ morphology in Rhipicephalus sanguineus sensu lato engorged females (Acari: Ixodidae) - Matos, Renata Silva [UNESP]; de Oliveira, Patrícia Rosa [UNESP]; Coelho, Letícia; de Paula, Luiza Gabriella Ferreira; Zeringota, Viviane; Carvalho Silva, Bianca; Monteiro, Caio; Daemon, Erik; Camargo-Mathias, Maria Izabel [UNESP] (Elsevier, 2020)
Thymol is a monoterpene with proven acaricidal activity on different tick species and life stages. The objective of this work was to evaluate the effect of thymol on the reproductive biology of engorged females of Rhipicephalus sanguineus sensu lato and the morphological changes caused in the cells of the tubular and accessory glands of Gené’s organ. The females were exposed to thymol by immersion. Seven groups were established: group I (distilled water), group II (30% ethanol), group III (thymol 1.25 mg/mL), group IV (thymol 2.5 mg/mL), group V (thymol 5.0 mg/mL), group VI (thymol 10.0 mg/mL), and group VII (thymol 20.0 mg/mL), with 20 replicates for each treatment. The ticks were kept in a BOD incubator at 27 ± 1 °C and RH > 80 ± 10%. Ten females from each group were evaluated daily until death, and the remaining ten were kept in the incubator under the same conditions for five days and then dissected for the removal of Gené’s organ to note possible damage to cell morphology by scanning electron microscopy (SEM) and hematoxylin-eosin (HE) techniques. Thymol demonstrated 63% and 98% efficacy in groups VI (10.0 mg/mL) and VII (20.0 mg/mL), respectively. In these groups, the cells of the tubular and accessory glands of Gené’s organ showed signs of damage: irregular eosin staining, rupture and deformation of the cellular limit, presence of fragmented nuclei, changes in cytoplasmic homogeneity and areas with deformation (folds) in the basal region.
Keywords: Accessory glands; Control; Histopathology; Monoterpene; Tubular glands